Taxonomy as a Genre and Cycle-Forming Pattern of “Fandorin corpus” by B. Akunin - A. B. Borunov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The issue of classification as the leading principle of organizing the set of texts by B. Akunin about Erast Fandorin are considered in the article. Particular attention is paid to the manifestation of this principle at the level of genre organization of texts and at the level of semantic and character components of works. The relevance of the study is due to the identification of the semantic constant of the metacycle about Erast Fandorin. It has been proved that the principle of taxonomy in the Fandorin corpus has two variants of manifestation — at the level of metacycle organization and at the level of semantics of the key motive of a classic detective — explaining the method used by the detective. The results of a comparative analysis of the image of Fandorin and his literary predecessors: detectives, derived in the texts of the authors of a classic detective story, are presented, and it is proved that Fandorin is the only one who explains in detail his method of investigation based on psychological classification. The authors dwell on the fact that the explanation of the method of investigation is an element of an intertextual game with the reader and at the same time, the opposition of the Russian detective to his English and American literary predecessors. At the same time, the principle of taxonomy is played up in the intertextual dialogue within the Fandorin corpus — other characters in this metacycle also resort to typing.